Ethnobotanical Study of Food Plant in Bentong Community from Barru Regency, South Sulawesi-Indonesia: KAJIAN ETNOBOTANI TUMBUHAN PANGAN MASYARAKAT SUKU BENTONG DI KABUPATEN BARRU SULAWESI SELATAN-INDONESIA - Dewi Sartik Amboupe; Alex Hartana; Y Purwanto (Media Konservasi, 2019)
The Bentong people lives in the village of Bulo-Bulo, Barru Regency, South Sulawesi. About 50 years ago, the community still lived a nomadic life, but today the community has settled. Knowledge about the use of plants as food ingredients by the people of the Bentong Tribe has not been recorded. This study aims to record and describe the utilization of food plant species of the Bentong tribe. Data collection through informant interviews, observations, and collection of herbarium specimens to be identified. Data were analyzed descriptively by examining plant species used as food ingredients and quantitative analysis using the index of cultural importance. The Bentong tribe uses 70 plant species as food ingredients including: 1) as a staple food consisting of 4 types namely 'kenrang' fruit (Ficus racemosa) and 'sikapa' tubers (Dioscorea hispida) when they were still nomadic and rice plants (Oryza sativa) and corn (Zea mays) after settling; 2) as a vegetable 34 species; 3) as a fruits 33 species; and 4) as a drink 5 species. ICS analysis results showed that the species that had the highest cultural importance index value were rice (100) followed by lontar (83), banana (78), coconut (48) and sugar palm (44). Keywords: Bentong, Bulo-Bulo Village, ethnobotany, nomadic